New energy frontier - Devare, Sudhir T. (ed.) (New Delhi, 2010)
The book effectively makes the point that the Bay of Bengal region holds a total population of 1.5 billion people, which in a relatively small area of land contains one quarter of humanity. The book by virtue of the innovative approach that it takes clearly establishes a case for some fresh thinking on energy policies within all the nations of the Bay of Bengal region. It brings out the benefits of coordination and cooperation rather than isolated plans and strategies based on narrow national perspectives
Keywords: Energy growth